Techno-economic Evaluation of a Forced Convection Solar Dryer - Jain, N K; Kothari, S; Mathur, A N (Journal of Agricultural Engineering, 2004)
A forced convection type solar dryer consisting of a flat-plate collector panel, a drying chamber and two blowers was used for drying of groundnut, ginger and garlic in comparison to an electrically operated tray type mechanical dryer. The benefit cost ratio for the solar dryer and mechanical dryer were found to be 1.56 and 1.18.